Ang pagbubuo ng mga salita sa Pilipino sa pamamagitan ng mga panlapi para sa mag-aaral na Chabacano sa unang taon ng mataas na paaralan - Pinlac, Angelina de Vera 1932- (s.n.], 1971)
This seminar paper presented instructional materials on the formation of words through the use of affixes. This study deals with the formation of nouns and adjectives through the use of the most common affixes: prefix, infix, and suffix. The methodology used was of tagmemic approach. This research aims to aid the learner in enriching his vocabulary and to serve as a model for language teachers in the preparation of instructional materials in Pilipino.